Pendampingan dan Fasilitasi Pendaftaran Merek UMKM Bantarsari Berbasis Kolaborasi Peran Pemerintah Desa dan Kampus - Purwaningsih, Endang; Santosa, Irwan; Yusuf, Chandra (ABDIMASY: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
The partners in this program include the Head of Bantarsari Village and his staff, representatives of associations, and Bantarsari Small and medium enterprises (SMEs). The partners face several issues: the absence of producer organizations, underutilization of information technology, unregistered product trademarks, limited online marketing reach, and low marketing management competence. The program aims to provide education and training on trademark legality and to assist and facilitate the creation and registration of trademarks. Activities are conducted using persuasive and participatory methods through lectures, discussions, training, mentoring, and trademark registration facilitation. Based on data analysis before and after the program implementation, it was concluded that the mentoring and facilitation of trademark registration for Bantarsari SMEs were effectively addressed through continuous outreach and mentoring. The average increase in the effectiveness of mentoring and facilitation activities for Bantarsari SMEs trademark registration based on the collaboration between the village government and the campus reached 31.4%.